Antibodies expose multiple weaknesses in the glycan shield of HIV. - Crispin, M; Bowden, T (Nature Publishing Group, 2013)
A shield of glycans coat the viral envelope proteins of the human immunodeficiency virus (HIV). Broadly neutralising antibodies can recognise this shield despite structural variation in these ‘self’ carbohydrate structures.